Corrosion resistance of ferrous alloys in tropical seawater environment - Yee, Seoh Soo (Fakulti Sains dan Teknologi, 2011)
Corrosion behaviour of AISI 1053 and AISI 304 ferrous alloys has been determined in seawater environment at room temperature. The effects of dissolved oxygen and circulating condition on both alloys have been investigated. Mass loss experiments have been conducted for duration of one year. Both alloys were exposed in conditions of seawater circulated with aeration, seawater circulated without aeration, seawater static without aeration and seawater static with aeration. Corrosion rate of both alloys in different exposure conditions ware obtained. The electrochemical behaviour of the alloys has been determined by Open Circuit Potential (OCP) and Polarization Resistance (7?p). The corrosion behaviour and electrochemical analysis of both alloys show identical behaviour. Overall, AISI 304 alloys were more resistance to seawater as compared to AISI 1053 alloys.